Matching the background of demonstrators with those of their students: does it make a difference : final report. - Kirkup, Les; Braun, Michael; Varadharajan, Meera; Buffler, Andy; Lubben, Fred (Department of Education, Office for Learning and Teaching, 2016)
Report from a project that aimed to enhance the value to students of undergraduate physics laboratories by examining student and demonstrator experiences and perceptions of the undergraduate physics laboratory. In particular it aimed to: examine the influence of alignment between the background, ambitions, and views on teaching and learning of students and their demonstrators on student engagement and satisfaction; explore students' and demonstrators' views about learning and teaching in the physics laboratory and how these views manifest themselves in student-demonstrator interactions; and investigate aspects of student-demonstrator interactions students consider helpful in increasing their engagement with laboratory work. As an outcome of this work, advice will be provided on demonstrators' recruitment, induction and professional development as well as commentary on issues impacting on student experiences in the undergraduate laboratory. [p.5, ed]